Targeting the Hexosamine Biosynthetic Pathway Prevents Plasmodium Developmental Cycle and Disease Pathology in Vertebrate Host - Gomes, Pollyanna Stephanie (2019)
Universidade Federal do Rio de Janeiro. Faculdade de Medicina. Instituto de Microbiologia. Rio de Janeiro, RJ, Brasil.